2008
DOI: 10.3390/medicina44120117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative results after implantation of hydrophilic acrylic or hydrophobic acrylic intraocular lens: Data of one-year prospective clinical study

Abstract: Objective. To evaluate and compare the impact of two sharp-edge optic foldable intraocular lenses (IOLs) of similar design made from different material (hydrophilic acrylic or hydrophobic acrylic) on visual function, anterior and posterior capsule opacification at one-year follow-up after cataract phacoemulsification. Material and methods. Seventy-two eyes of 72 patients scheduled for cataract surgery were included in a prospective clinical study. Two foldable sharp-edge optic posterior chamber acrylic IOLs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
4
0
1
Order By: Relevance
“…These properties have been also linked with ACCS development, while hydrophobic IOLs appear to have better biocompatibility in terms of anterior capsule contraction syndrome and posterior capsular opacification [14,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…These properties have been also linked with ACCS development, while hydrophobic IOLs appear to have better biocompatibility in terms of anterior capsule contraction syndrome and posterior capsular opacification [14,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Although hydrophilic acrylic material has better uveal biocompatibility, lower adhesion of bacteria and silicone oil, and less incidence of glare, its weak adhesion to type IV collagen leads to an increased incidence of fibrosis, which is more likely to lead to the occurrence of CCS [25][26][27]. The hydrophobic acrylate IOL can inhibit the migration of LEC to the optical zone and loops, thereby reducing the occurrence of CCS [22,28,29]. In this case, both eyes of the patient used hydrophilic acrylic IOL, which may also be one of the risk factors for the rapid occurrence of CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Not proven in the Sensar IOL, hydrophobic acrylic has bioadhesive characteristics that enhance the adhesion of IOL to the capsular bag and leads to less proliferation of LECs and anterior and posterior capsule fibrosis, with successive alleviation of capsule contraction and optic movement [ 22 , 23 ]. Several studies have reported that anterior capsule contraction was significantly greater after hydrophilic IOL implantation than after hydrophobic IOL implantation [ 24 26 ]. We expect that more definite results may be found in further studies using hydrophilic acrylic IOLs instead of hydrophobic acrylic IOLs.…”
Section: Discussionmentioning
confidence: 99%